THE ANTHELMINTICS EFFECT OF MOMORDICA CHARANTIA L. LEAVES AND ANDROGRAPHIS PANICULATA NESS. FROM INDONESIA - Nur Chastity, Canny; Lugi Yuwono, Karsa; Utami, Ummi; Ayu AP, Prala; Priscillah, Wildan; Sutrisna, Em (International Journal of Ayurveda and Pharma Research, 2015)
Momordica charantia L. leaves and Andrographis paniculata Ness. leaves were traditionally used as anthelmintic in Indonesia. Objective: This study aims at examining the anthelmintic effects of 70% ethanolic extract of Momordica charantia L. leaves and Andrographis paniculata Ness. leaves. Material and Method: This research was an experimental research with only post test controlled group design. The samples were 72 Ascaris suum worms, divided into 8 groups. The first group was treated by NaCl 0.9% solution as negative control, the second group was treated by pyrantel pamoate as positive control in 0.236 % concentration. The third, fourth and fifth group were treated by 70% ethanolic extract of Momordica charantia L. in 20%, 40%, 80% concentrations respectively. The sixth, seventh and eighth groups were treated by 70% ethanolic extract of Androgaphis paniculata Ness. in 20%, 40% 80% concentrations respectively. Data were collected by observation of total mortality time of Ascaris suum worm every 1 hour. The anthelmintic effects test analysis is performed by Kruskal Wallis test and followed by Mann Whitney test with significancy level at p <0.05. Result: There are is significant difference between the 70% ethanolic extract of Momordica charantia L (20%, 40%, 80%) and Andrographis paniculata Ness. (20%,40%,80%) with control negative with P value <0.05 by Mann whitney test. Conclusion: The 70% ethanolic extract of Momordica charantia L. and Andrographis paniculata Ness. leaves have potential as anthelmintic.